From the double pendulum model to full-body simulation: evolution of golf swing modeling - Betzler, N.; Monk, S.; Wallace, E.; Otto, S. R.; Shan, G. (Sports Technology, 2008)
Golf is one of the most popular sports worldwide. Scientific research into golf has grown substantially over the past four decades. This article reviews the biomechanical models of the golf swing, focusing on how these models can aid understanding of golf biomechanics and the fitting of golf clubs to individual players. It is shown that models range in complexity from the conventional double pendulum model to full-body simulations that include sub-models. The usefulness of any model or simulation is ultimately determined by the assumptions included and the model's complexity. The article summarizes the established areas of golf swing modeling and simulation, discusses the assumptions made by those models, and identifies areas where more research and further development are needed.